PEMBELAJARAN SAINTIFIK BERBASIS ICT UNTUK MENINGKATKAN KUALITAS MENGAJAR GURU DI KECAMATAN CAGAK KABUPATEN SUBANG JAWA BARAT - Ika Mustika; Latifah Latifah; Restu Bias Primandhika (IKIP SILIWANGI, 2020)
In the 2013 curriculum (K-13) there was a paradigm shift in learning that initially centered on the teacher (teacher-centered) to be centered on students (student-centered). Based on the results of observations made to teachers in the Cagak District Subang District, West Java, the application of the scientific approach is not maximally carried out, this is because according to the narrative of the teachers in the area the use of science in the learning process takes a long time. To facilitate the steps of the scientific approach carried out by teachers in the Subang District of West Java and the material learned is easily understood by students, ICT will be very helpful, at the stage of identifying students can use the internet to find information and then formulate a problem, compile a problem, testing hypotheses, collecting data, processing, and analyzing data can be easily carried out with the help of internet media, then at the stage of compiling reports students can use laptops to store the results of material that has been sought and studied, at the presentation stage students can use PowerPoint media to makes it easy to present the material so that the material presented is more interesting